21‐3: Reliability of Coplanar Oxide TFTs : Analysis and Improvement. Issue 1 (May 2017) - Baeck, Ju-Heyuck; Oh, Saeroonter; Lee, Dohyung; Park, Taeuk; Bae, Jong Uk; Park, Kwon-Shik; Yoon, SooYong; Kang, InByeong
Abstract : We confirm that the PBTS instability of coplanar InGaZnO TFTs can be improved through the minimization of Non‐Bridging Oxygen Hole Centers (NBOHC) and optimization of hydrogen passivation in the GI/ACT interface region. The quantitative analysis of hydrogen and oxygen in each region are obtained from physical property measurements. Trap density in GI/ACT interface layer is obtained by photonic capacitance‐voltage measurements which are correlated with PBTS characteristics. A decrease of under coordinated bonding states lessens electron trap density, which brings improvement in PBTS from Vth = 2.61V to 0.21V by process optimization.